Environmental Cost Accounting: Behind the Major Project for the Construction of a Covid-19 Hazardous Waste Management Facility - Istidha Nur Amanah (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
After focusing on handling Covid-19, all countries face Covid-19 medical waste. Covid-19 medical waste in Indonesia reached 18,460 tons as of 27 July 2021. The number of waste management facilities did not follow the increased volume of hazardous medical waste. The government has compiled the construction of hazardous medical waste management facilities from health facilities into the Government Work Plan (RKP) for 2022. The budget allocated for the construction facility is quite large. An analysis is needed from the budget management perspective to achieve the right goals and objectives of the program. This research used literature studies from various relevant sources. Data analysis uses an environmental cost accounting perspective consisting of prevention, detection, and internal and external failure costs. The results show that from all aspects of these costs, the government has fulfilled them through the main program and supporting programs. Each program has a budget but no details of every need. The government has not budgeted for technology development, human resource development, collaboration with the private sector, and other impacts that have the potential to hinder the management of hazardous medical waste from health facilities.